(untitled) (Sustainability in Debate, 2020)
Geotechnologies are a set of technologies geared towards collection, processing, analysis and availability of information with geographic reference. Therefore, the objective of this research is to demonstrate through the spatial analysis the environmental characteristics of an enterprise located in the municipality of Currais ”“ PI, object of the environmental licensing procedure of the state competent body, using the tools of geotechnologies. The methodology consisted in using the Geographic Information System Quantum GIS (QGIS) for the creation and processing of the geographic database. Through the generation of thematic maps, it was possible to conclude that the uses of geotechnologies aid in the control and environmental monitoring, in which, it facilitates the visualization and characterization of several environmental features in the environmental licensing procedure. It was also possible to identify the areas that deserve greater attention from the environmental agency due to some damage to the environment, as well as, it assists in environmental inspection and current legislation.